Clinical evaluation of mark induced dermatitis on health care workers during COVID-19 pandemic: a cross sectional study - I., Sushma; Simon, Nivin; Pravin, A. J. S.; Padmaprasad, M. K.; Vijayabharathi, M.; Varghese, Mulamoottil George (International Journal of Research in Dermatology, 2021)
Background: Mask induced dermatitis is common among health care workers now because of the obligatory use of facemask for a longer period during COVID-19, the clinical features vary. Very few studies could be conducted due to the COVID induced constraints. Studies regarding reactions to face masks in health workers published to date are limited and hence we decided to do this study. The objective of this study was to find out the clinical presentations of mask induced dermatitis due to long term use of facemask on healthcare workers during COVID-19 pandemic. Methods: A cross sectional study was conducted among 40 healthcare workers attend our OPD with face mask for 6 months. After getting informed written consent clinical evaluation was made by history and dermatologic examination. Results: Total 40 health care professionals between the age group of 21-50 years (17 females and 23 males) came to our OPD with complaints of itching and dryness with signs of erythema, scaling, papules for 6 months duration. Out of them, 15 (37.5%) patients had exacerbation of pre-existing dermatoses like atopic dermatitis, seborrheic dermatitis, chronic urticaria, acne. 10 patients (25%) had irritant contact dermatitis 7 patients (17.5%) had sweat-induced dermatitis, 4 patients (10%) had dermatitis due to sponge strip at the nasal bridge, 4 patients (10%) had dermatitis due to vehement use of ear loop involving retroauricular region. Conclusions: This study showed that wearing face masks results in the development and aggravation of other skin diseases due to various causes. Itch can induce scratching and thus lead to inappropriate use of face masks, which could compromise their function.